An assessment framework for climate-proof nature-based solutions - Calliari, Elisa; Staccione, Andrea; Mysiak, Jaroslav (The Science of the total environment, 2019)
Raising interest in ‘nature-based solutions’ (NBS) has inspired attempts to organise their principles and qualities within comprehensive and internally consistent evaluation frameworks, so as to demonstrate the superior performance of ‘working with nature’. However, the proposed frameworks stop short of taking into account the changing conditions in which NBS are set to operate. Climate change, in particular, can alter ecosystems and their services, and may undermine the performance of green solutions that rely on them. We present here a ‘dynamic’ assessment framework that explicitly accounts for the impact of climate change on the effectiveness of the proposed NBS. The framework is based on an innovative approach that integrates system analysis and backcasting. Although it has not yet been applied to the NBS context, backcasting is well-suited to seize the transformational character of NBS, as it encourages ‘breakthrough’ leaps rather than incremental improvements. Our framework factors in the multifunctional character of NBS and is designed to capture associated direct benefits/costs and co-benefits/costs. It is meant to be applied ex ante to ideally support the choice between innovative NBS and traditional options, in an effort to respond to the societal challenges identified by the EU Research & Innovation agenda on the environment. [Display omitted] •Assessment frameworks should evaluate NBS' effectiveness under future climate conditions.•We propose an assessment framework based on systems analysis and backcasting.•The framework can be applied to support the choice between NBS and traditional options.•The framework factors NBS' multifunctionality and assesses (in)direct benefits/costs.•Ecosystem disservices are explicitly factored in the assessment as co-costs.